Review of: “Verónica Ramírez, Elisa Sevilla y Agustí Nieto-Galan. eds. (2022). Astronomía, literatura y espiritismo. Camille Flammarion en América Latina. RIL Editores, Universidad Adolfo Ibáñez. - Barquero Morice, Pablo (2022)
With diverse themes that encourage young minds to delve into new lines of work; this is what is produced in the book: Astronomy, literature and spiritualism. Camille Flammarion in Latin America, edited by Verónica Ramírez, Elisa Sevilla and Agustín Nieto-Galan.